Riwayat Hipertensi pada Kehamilan Sebelumnya dengan Preeklampsia pada Ibu Bersalin - I Dewa Ayu Ketut Surinati; Sur Suratiah (Jurnal Gema Keperawatan, 2017)
The purpose of this researce is to know the relationship of hypertension history in previous pregnancy with preeclampsia in maternity mothers. This researce is quantitative researce that using retrospective design, conduced on 174 maternals who has preeclampsia. The sampling technique is using one of the nonprobability sampling, that is purposive sampling The chi square test result of value p = 0.000 (p value ≤ 0,05) dan Odds Ratio (OR) = 2,065. It means that there is a significant relationship between hypertension history in previous pregnancy with preeclampsia.